Novel antiviral effect of lithium chloride on mammalian orthoreoviruses in vitro. (April 2016) - Chen, Ye; Kong, Deyang; Cai, Gengyuan; Jiang, Zhiguo; Jiao, Yiren; Shi, Yuzhen; Li, Huaqin; Wang, Chong
Abstract: Reovirus not only causes considerable economic loss in the swine industry of the United States and other countries, but also threatens the public health due to its zoonotic potential. According to previous reports, LiCl has antiviral activity against a number of viruses. The inhibitory effects of LiCl on reovirus life cycle in Vero cells were evaluated. The unpaired t-test and one-way ANOVA were used to analyze the differences between experimental groups. We first found that LiCl treatment significantly inhibited reovirus replication in a dose-dependent manner. Furthermore, we found that this antiviral activity of LiCl targets the early stage of viral replication. LiCl could be a potential drug against reovirus infection. Highlights: We first found that LiCl treatment significantly inhibited reovirus replication. We first found that this antiviral activity of LiCl targets the early stage of viral replication. LiCl could be a potential drug against reovirus infection.